Classroom Concordancing and Second Language Motivational Self-System: A Data-Driven Learning Approach - Zare, Javad; Karimpour, Sedigheh (Frontiers in Psychology, 2022)
Research shows that exploring language corpora through data-driven learning (DDL) approach plays a significant role in language learning. Nevertheless, it is not clear if using concordancing as an application of DDL affects the learners’ second language motivation. To address this gap, the current study adopted a triangulation design, validating quantitative data model, and a quasi-experimental (comparison group, pretest-posttest) design. Ninety English-major university students with an intermediate level of English language proficiency, divided into control and experimental groups, took part in the study. Drawing on a second language motivational self system questionnaire, the findings of the study did not result in any statistically significant differences between the students in their second language motivational self system. Altogether, the students found learning English through a DDL approach with concordancing less motivating than receiving explicit instruction. The study has implications for language teaching and learning.